Exploring perceptions of and supporting dyslexia in teachers in higher education in STEM. Issue 6 (1st November 2020) - Hiscock, Jennifer; Leigh, Jennifer
ABSTRACT: There is much literature focused on supporting students diagnosed with learning difficulties within higher education, in particular those with dyslexia. However, there is relatively little that discusses perceptions of and support for academics who have been diagnosed with the same learning difficulties. Although statistics from the Higher Education Statistics Authority suggest that percentages of staff declaring that they have dyslexia are much lower than those of undergraduate or postgraduate students, anecdotally media and social media suggest there is a sizeable population of academics who have this neurodiversity. In this paper we explore perceptions of dyslexia, and suggest practical ways in which to support new academics with or without a diagnosis.